Framing The South China Sea: How Media Shapes Perceptions Through Rhetorical Power - Bana Supeno; Amiruddin Hadi Wibowo (Universitas Islam Negeri Palopo, 2025)
This study examines the role of media in shaping public perception of the South China Sea (SCS) dispute by analyzing the coverage of CNBC and Kompas during June and July 2020. Utilizing Cicero’s Amplification techniques such as repetition, iteration, word doubling, and gradual intensification. This research explores how these rhetorical strategies reinforce key points and shape narratives. Through a detailed discourse analysis, the study reveals that CNBC focused on global economic impacts and geopolitical rivalry, resonating with an international audience, while Kompas emphasized regional stability and ASEAN’s role, appealing to Southeast Asian readers. The findings highlight the media’s power in crafting compelling and memorable arguments, influencing public opinion on international conflicts. Limitations of the study include the analysis of only two media outlets over a specific period. Future research could expand the scope by including more media sources, extending the timeframe, and examining the impact of social media. Understanding these rhetorical strategies is crucial for policymakers, media professionals, and the public to critically assess media reports and their influence on public perception.